Managing forests and improving the livelihoods of forest-dependent people: reflections on CIFOR’s social science research in relation to its mandate for generalisable strategic research - Vayda, A.P. (1997)
CIFOR has been actively engaged in field research in Indonesia focussing particularly on the role of forests and forest products in generating sustainable livelihoods for local users. Issues such as incentives and institutional structures for equitable and sustainable management systems have been highlighted in this research, which has been undertaken with the active co-operation of local NGOs. During Professor Vayda's residency in CIFOR as a Distinguished Visiting Scholar, he was requested to conduct a review of CIFOR's social science research, particularly the connections between this Project and CIFOR's other related research on Biodiversity and Non-timber Forest Products. In this review he has assessed the extent to which CIFOR should seek or expect to find "generalisable" research findings to such questions, and whether this particular set of activities was well-located and well-targeted to attain that objective. His report has led to some modification and refinement of this very important component of CIFOR's overall programme.